Accuracy and preference assessment of prefilled insulin pen versus vial and syringe with diabetes patients, caregivers, and healthcare professionals. (May 2013) - Pfützner, Andreas; Bailey, Timothy; Campos, Carlos; Kahn, Douglas; Ambers, Ellen; Niemeyer, Marcus; Guerrero, German; Klonoff, David; Nayberg, Irina
Abstract Objectives: The primary objective of this study was to investigate the dosing accuracy of the new prefilled FlexTouch* insulin pen (FT) in comparison to conventional vial and syringe (V&S) when used by patients (Pts), caregivers (CG) and healthcare professionals (HCPs). Methods: A total of 120 subjects participated in the trial (40 diabetes patients aged 61 ± 11 [mean ± SD] yrs, 20 caregivers [parents and other relatives], 20 physicians, and 40 nurses/certified diabetes educators). The participants were introduced to the devices in randomized order and were asked to perform injections of 5, 25, 43 and 79 IU doses into laboratory tubes. Dosing accuracy was analyzed by weighing the tubes on a pharmaceutical balance and calculating the mean absolute deviation (MAD) from the intended doses. After completing a device assessment questionnaire, Patient Perception Questionnaire (PPQ), with questions regarding device design and performance, the procedure was repeated for the other device, and the patients were finally asked to complete a device preference questionnaire (DPQ). Results: Dosing accuracy was significantly better for FT when used by any of the cohorts at all doses. (MAD ± SD for FT/V&S; 5 IU: 0.4 ± 0.4/0.6 ± 0.6 IU; 25 IU: 0.3 ± 0.4/0.7 ± 0.9 IU; 43 IU: 0.4 ± 0.4/0.9 ± 1.2 IU; 79 IU: 0.5 ± 0.5/1.7 ± 1.6 IU, p < 0.005 for all doses). Dosing accuracy with FT for all three subgroups was comparable (patients: 0.35–0.59 IU; HCP&CG: 0.29–0.54 IU; n.s.). Dosing accuracy with V&S for all three subgroups was not comparable: HCP and CG performed much better with V&S than patients and delivered the doses with significantly higher accuracy (range of mean MAD; patients: 0.81–2.54 IU; HCP&CG: 0.51–1.30 IU, p < 0.005 at all doses). FT was ranked superior to V&S for all aspects of the PPQ. In the DPQ, 93% of the patients voted for FT (neutral: 5%, V&S: 2%), (CG: 100%/0%/0%; HCPs: 85%/2%/13%; p < 0.001 in all cases). Conclusion: FT, compared to V&S, was more accurate at all tested doses and was used with similar accuracy by patients, HCPs, and CGs. Using questionnaires only, and without dexterity assessment, study participants rated FT higher than V&S in every component of the PPQ and the vast majority of them preferred FT. These findings may point to a better alternative for dosing accuracy and improved adherence when using the new prefilled insulin pen compared to V&S for insulin delivery in patients with diabetes.